An Analysis of Self-Directed Learning in Speaking Class During Pandemic Covid-19 - Riswanto, Riswanto; Haryanto, Endang; Maisyarah, Maisyarah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The COVID-19 pandemic is a situation where students are responsible and independent in their learning. During the COVID-19 pandemic, the Minister of Education and Culture decided to switch teaching and learning activities in the classroom to an online system. This study aims to determine the level of self-directed learning independence in speaking class and the influencing factors. This study was designed as descriptive quantitative research using Likert scale questionnaires and interviews. The subjects of this study were students of SMAN 06 Bengkulu Tengah. Data analysis was carried out using the formula proposed by Sudjana to determine the percentage of students' scores. The results show that more than 64%, or half of the students, have fairly high levels of self-directed learning in the speaking class. Based on the findings and discussions, as a result of the COVID-19 epidemic, the use of online learning in educational practice has gone well because students already have a fairly high level of independence.Â